Hepatitis B Virus Infection and Response to Antiretroviral Therapy (ART) in a South African ART Program - Hoffmann, Christopher J. (2008)
BACKGROUND: Coinfection with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) is common in Africa; however, the impact of HBV infection on the outcomes of antiretroviral therapy programs is unclear. We evaluated the impact of chronic hepatitis B on HIV virologic response, changes in CD4 cell count, hepatotoxicity, and mortality among Africans receiving highly active antiretroviral therapy (HAART). METHODS: We conducted a retrospective cohort study involving a workplace HAART program in South Africa. Participants received HAART according to a protocol and were followed up for up to 72 weeks. On the basis of pre-HAART serum assays, patients were classified as being hepatitis B surface antigen (HBsAg) negative, HBsAg positive with a low HBV DNA level (≤1 × 10(4) copies/mL), and HBsAg positive with a high HBV DNA level (>1 × 10(4) copies/mL). The relationships between HBV status and HIV RNA suppression, change in CD4 cell count, mortality, and hepatotoxicity were assessed with use of regression techniques. RESULTS: Five hundred thirty-seven individuals fulfilled the inclusion criteria; 431 (80.3%) of these patients were HBsAg negative, 60 (11.2%) were HBsAg positive with a low HBV DNA level, and 46 (8.6%) were HBsAg positive with a high HBV DNA level. All groups had similar rates of HIV RNA suppression (P =.61), CD4 cell count increases (P =.75), and mortality (17 total deaths; P =.11) for up to 72 weeks after the initiation of HAART. Baseline transaminase levels were highest in the group with high HBV DNA levels (P =.004). Hepatotoxicity was similar between the HBsAg-negative group and the group with low HBV DNA levels but was higher in the group with high HBV DNA levels (incidence rate ratio, 4.4). CONCLUSIONS: We revealed that HBV status does not affect HIV RNA suppression, CD4 cell count response, or mortality during the first 72 weeks of HAART in an African setting. The risk of HBV-associated hepatotoxicity, however, is associated with the baseline HBV DNA level.